Room temperature multiferroicity in Aurivillius compounds Bi6Fe2−xNixTi3O18 (0≤x≤1). Issue 5 (1st April 2017) - Xiong, P.; Yang, J.; Qin, Y.F.; Huang, W.J.; Tang, X.W.; Yin, L.H.; Song, W.H.; Dai, J.M.; Zhu, X.B.; Sun, Y.P.
Abstract: We investigate the structural, magnetic, ferroelectric, and dielectric properties of Bi6 Fe2− x Ni x Ti3 O18 (0≤ x ≤1). The coexistence of ferroelectricity and ferromagnetism were observed at room temperature for the Ni-doped samples. The ferromagnetism in Bi6 Fe2− x Ni x Ti3 O18 can be understood in terms of spin canting of the antiferromagnetic coupling of the Fe-based and Ni-based sublattices via Dzyaloshinsky-Moriya interaction. Moreover, the substitution of Ni for Fe was effective for the enhancement of ferroelectric properties. The x =0.6 sample exhibits a maximum remnant polarization P r of 37.8 μC/cm 2 because of a lower leakage current. The rather large activation energy in the x =0 and 0.2 samples implies that the relaxation process may be not associated with the thermal motion of oxygen vacancies inside the bulk.